2020
DOI: 10.36366/frontiers.v32ivirtual.464
|View full text |Cite
|
Sign up to set email alerts
|

Introduction: Recent Research in Assessment in Education Abroad

Abstract: The Guest Editors introduce their virtual issue on Recent Resarch in Assessment in Education Abroad, which curates past articles published in Frontiers on the topic. Click on the links beside each selected article in the REFERENCES section below to read the full article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…To our best knowledge, there have been no other pedagogical course design attempts that do not involve study abroad but instead rely on a glocal approach in response to the gaps and limitations in study abroad programs. Furthermore, we found no course designs that utilize assessment as a method of learning as described in the literature (Acheson et al, 2020;Rowe, 2012). To fill this gap, the study results reported here are guided by two research questions.…”
Section: Pedagogical Application In a Glocal Settingmentioning
confidence: 94%
See 4 more Smart Citations
“…To our best knowledge, there have been no other pedagogical course design attempts that do not involve study abroad but instead rely on a glocal approach in response to the gaps and limitations in study abroad programs. Furthermore, we found no course designs that utilize assessment as a method of learning as described in the literature (Acheson et al, 2020;Rowe, 2012). To fill this gap, the study results reported here are guided by two research questions.…”
Section: Pedagogical Application In a Glocal Settingmentioning
confidence: 94%
“…However, we are also living in a time when "people have found more and more ways to distance themselves from each other, and to protect their own understanding of the world" (Berdrow et al, 2020, p. 1). Cultural immersion admittedly offers numerous benefits for open-minded students, but this study suggests another option when study abroad is not possible or in combination with study abroad -a glocal classroom with a strong focus on assessment that provides awareness into cognition and effective intercultural behaviors through ongoing monitoring and feedback (Acheson, et al, 2020;Rowe, 2012). Hence, our proposed pedagogy utilizes assessment as a learning tool to provoke self-awareness, as well as ongoing formative assessment in the form of weekly feedback (peer and instructor), self-feedback, reflection, and the summative assessment in a final PDP report to inspire the development of metacognition and intercultural skills (Morris et al, 2019).…”
Section: Research Limitations and Future Directionsmentioning
confidence: 96%
See 3 more Smart Citations